Supravalvular aortic stenosis associated with a deletion disrupting the elastin gene. - Ewart, A K (1994)
Supravalvular aortic stenosis (SVAS) is an inherited vascular disease that can cause heart failure and death. SVAS can be inherited as an autosomal dominant trait or as part of a developmental disorder, Williams syndrome (WS). In recent studies we presented evidence suggesting that a translocation disrupting the elastin gene caused SVAS in one family while deletions involving the entire elastin locus caused WS. In this study, pulsed-field, PCR, and Southern analyses showed that a 100-kb deletion of the 3' end of the elastin gene cosegregated with the disease in another SVAS family. DNA sequence analysis localized the breakpoint between elastin exons 27 and 28, the same region disrupted by the SVAS-associated translocation. These data indicate that mutations in the elastin gene cause SVAS and suggest that elastin exons 28-36 may encode critical domains for vascular development.